Operation State Evaluation Method of Smart Distribution Network Based on Free Probability Theory - Zhang, Jiaxin; Wang, Bo; Wang, Hongxia; Ma, Hengrui; Ma, Fuqi; Li, Yifan; Zhang, Yingchen (Frontiers in Energy Research, 2022)
In view of the current situation that the new generation of smart grids with “double high” characteristics is in urgent need of effective state evaluation methods due to the characteristics of strong volatility and diverse demands, a method of operation state evaluation of smart distribution networks based on free probability theory is proposed, which is combined with high-order moment indexes to describe the operation trajectory of distribution networks from a data-driven perspective. First, the state assessment problem of smart distribution networks is modeled as a binary hypothesis testing problem, and the asymptotic free equation is established based on free probability theory to provide a framework for state assessment of distribution networks. Then, a high-order moment evaluation index is proposed, combined with the sliding time window processing, and the high-order moment sequence was obtained based on the high-dimensional data of the distribution network, which is used to describe the state evolution of the distribution network. Finally, this method is applied to a certain 110-kV distribution network. The analysis of an example shows that the proposed evaluation framework and indicators can effectively reflect the data changes in the distribution network and support the state assessment and evolution analysis of the distribution network.